Effect of Sodium Fluoride and Aluminum Sulfate Salts on PVA Polymer Film Synthesized Using Casting Technology - Kalf, Duha Sabeeh; Jasim, Saif Khalel (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2026)
Polymer films were manufactured from polyvinyl alcohol (PVA) doped with a concentration of sodium fluoride (NaF) and aluminum sulfate (Al2(SO4)3) salts via the solution casting method. The differences in crystallinity and transformation temperatures of solid polymer electrolyte sheets were analyzed using differential scanning calorimetry (DSC). The formation of a complex structure between PVA polymer and a salt were confirmed using Fourier transform infrared spectroscopy (FTIR). Absorption spectra were obtained in the wavelength range of 200–1200 nm and analyzed using the absorption equation for amorphous materials. The energy gap values showed a clear dependence on the concentration of sodium fluoride and aluminum sulfate. The indirect energy gap was determined and analyzed in relation to the integration of charge-transfer complexes within the grafted materials.